Enhancing Community Knowledge on Sawdust Waste Utilization through Particleboard Manufacturing - Silvia Uthari Nuzaverra Mayang Mangurai; Hikma Yanti; Yulanda Yulanda; Sarma Siahaan; Sarah Augustina (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2026)
Background: Sawdust is one of the most abundant by-products of wood utilization in rural communities near forest areas. In Manggang Village, West Kalimantan, sawdust waste is commonly piled up or burned, causing environmental problems. This community service activity aimed to introduce the utilization of sawdust waste as a raw material for particleboard production to increase its economic value and reduce environmental pollution. Contribution: The activity promoted community awareness of sawdust waste utilization through the introduction of particleboard production as a value-added product. Method: The community service activity was conducted in Manggang Village, Landak Regency, West Kalimantan. The implementation stages included planning, material preparation, demonstration of particleboard manufacturing, monitoring, and evaluation. Results: Community understanding of environmental pollution caused by sawdust waste increased from 30% to 67%. Knowledge of particleboard manufacturing increased from 50% to 90%. Understanding of particleboard utilization as furniture increased from 43% to 100% and awareness of its economic potential increased from 50% to 100%. The results indicate that the activity successfully enhanced both environmental awareness and practical skills related to sawdust utilization. Conclusion: The activity successfully improved community knowledge regarding sawdust waste utilization and particleboard manufacturing. The activity demonstrated that community education can support environmentally sustainable waste management while creating opportunities for value-added products in rural communities.